Consumer Factors Buying Organic Products in North Sumatera - Effendi, Ihsan; Shunhaji, Akhmad (Esensi: Jurnal Bisnis dan Manajemen, 2020)
The market condition for organic products in Sumatera Utara is still very small. This can be seen from the very few companies engaged in organic products. The market is very small due to low consumer awareness and consumer knowledge of organic products. This research was conducted to analyze the characteristics and behavior of consumers about organic products in Sumatera utara. The locations of research activities are Medan, Binjai, Deli Serdang, Serdang Bedagei and Langkat. In addition, the lack of involvement of local governments and related institutions in encouraging the development of organic products is indicated by the low level of commitment in developing organic products in Sumatera utara. The results of this study indicate that organic knowledge, environmental science, health science, pricing and subjective norms are the factors that determine whether consumers buy organic products